Investigations on anomalous behavior of ionic conductivity in NaPF6 salt loaded hydroxyethyl cellulose biodegradable polymer electrolyte for energy storage applications. (9th February 2023) - Chavan, Chetan; Bhajantri, Rajashekhar F.; Cyriac, Vipin; Ismayil,; Bulla, Soumya S.; Sakthipandi, K.
Abstract: This article investigates the influence of NaPF6 salt content (0–30 wt.% in a varying interval of 5 wt.%) on the structural, electrical, and biodegradable properties of HEC/NaPF6 solid biopolymer electrolyte (SBE) films. The interaction of salt with the HEC polymer matrix is confirmed by FTIR and SEM studies. The elemental composition and mapping confirm the appearance of NaPF6 moieties in the HEC polymer matrix. XRD deconvolution reveals that HEC samples with 20 wt.% (H4) and 10 wt.% of salt (H2) have a significantly lower crystallinity index than pure HEC polymer. The H2 and H4 samples show the highest room temperature conductivity values (1.62 × 10 −5 and 1.13 × 10 −5 S cm −1, respectively) among all other prepared samples since carrier concentration influences the ionic conductivity and shares a similar order of conductivity. Thus, the H2 and H4 samples are employed as electrolyte separators in the sodium ion battery, and the results suggest that the H2‐based electrolyte system is more significant. Battery matrices like open circuit voltage (V), current density (μA cm −2 ), power density (mW kg −1 ), energy density (Wh kg −1 ) and discharge capacity (μA h −1 ) were calculated and found to be 2.48, 5.49, 44.60, 1.69, and 71.05, respectively for H2 electrolyte based cell. Wagner polarization reveals that H2 and H4 constitute the predominant charge carriers (ions) with total ion transference numbers of ⁓0.98 and ⁓0.99, respectively. To evaluate sample degradability, H2 and H4 samples were subjected to 20 and 5‐day biodegradation processes, during which the polymers completely (100%) broke down.